Costa Rica : Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report ;, 2016)
This paper looks at the following important issues pertaining to the economy of Costa Rica: micro-financial linkages, financial sector vulnerabilities, monetary policy stance, financial deepening in Costa Rica, financial inclusion in Costa Rica, recent fiscal developments and medium-term sustainability, and female labor force participation in Costa Rica. This paper discusses linkages between the Costa Rican real economy and financial sector. Although increasingly diversified, the Costa Rican financial system is centered on banking intermediation. The banking system is highly segmented and heavily dollarized. To assess the adequacy of the current monetary policy stance, this paper estimates the neutral monetary policy interest rate.